A new integrated care pathway for ambulance attended severe hypoglycaemia in the East of England: The Eastern Academic Health Science Network (EAHSN) model. (November 2017) - Sampson, Michael; Bailey, Marcus; Clark, John; Evans, Mark L.; Fong, Rebekah; Hall, Helen; Hambling, Clare; Hadley-Brown, Martin; Morrish, Nick; Murphy, Helen; Rayman, Gerry A.; Vithian, Karunakaran; et al.
Abstract: Aims: We developed a new clinical integrated pathway linking a regional Ambulance Trust with a severe hypoglycaemia (SH) prevention team. We present clinical data from the first 2000 emergency calls taken through this new clinical pathway in the East of England. Methods: SH patients attended by Ambulance crew receive written information on SH avoidance, and are contacted for further education through a new regional SH prevention team. All patients are contacted unless they actively decline. Results: Median age (IQR) was 67 (50–80) years, 23.6% of calls were for patients over 80 years old, and patients more than 90 years old were more common than 20–25 year olds in this population. Most calls were for patients (84.9%) who were insulin treated, even those over 80 years (75%). One - third of patients attended after a call were unconscious on attendance. 5.6% of patients in this call population had 3 or more ambulance call outs, and they generated 17.6% of all calls. In total, 728 episodes (36.4%) were repeat calls. Insulin related events were clinically more severe than oral hypoglycaemic related events. Patients conveyed to hospitals (13.8%) were significantly older, with poorer recovery in biochemical hypoglycaemia after ambulance crew attendance. Only 19 (1%) opted out of further contact. Patients were contacted by the SH prevention team after a median 3 (0–6) days. The most common patient self - reported cause for their SH episode was related to perceived errors in insulin management (31.4%). Conclusions: This new clinical service is simple, acceptable to patients, and a translatable model for prevention of recurrent SH in this largely elderly insulin treated SH population.